Utilize azimuthal correlation to examine the collective flow influence caused by the reaction between $$^{84}$$Kr nuclei and emulsion nuclei at 1 A GeV - Singh, Manoj Kumar; Kumari, Babita; Attri, Kajal (Journal of the Korean Physical Society, 2024)
The expansion and decay of excited and compressed nuclear matter produced in heavy-ion collisions across a broad range of incident energies are largely dependent on collective fow. Hydrodynamic theories suggest that the fuid-like behavior of nuclear matter produces a substantial azimuthal correlation in the particle emission. The greatest opportunity to discover nuclear matter compressibility and, indirectly, the nuclear equation of state is through precise measurements of collective fow. The collective fow of projectile fragments (PFs) of charge Z ≥ 2 produced in 84Kr in interacts with emulsion (composite target) and Ag(Br) target at 1 A GeV for NPF ≥ 3 and N훼 ≥ 3 has been evaluated using azimuthal correlation functions. The collective fow is observed to be the most pronounced in semi-central collisions. The amplitude of the collective fow appears to be pretty stable at relativistic energy, according to our observation. Additionally, the obtained outcomes are compared to other existing experimental data. KCI Citation Count: 0